Artificial Intelligence–Based Administration and Students’ Spirituality in Islamic Education: A Tarbiyah-Oriented Pedagogical Ecology - Zain, Jasmine Mutiara; Shodiq, Sadam Fajar (Faculty of Tarbiyah and Teacher Training, Universitas Islam Negeri Alauddin Makassar, 2026)
The rapid integration of Artificial Intelligence (AI) into educational administration and learning has created both opportunities and challenges for Islamic education, particularly regarding students’ cognitive engagement and spiritual development. While AI-supported administration enhances efficiency and data-driven decision-making, its implications for students’ spirituality and moral formation remain underexplored. This study investigates how AI-enabled administrative practices shape learning environments and students’ spiritual development in Islamic secondary schools. Employing a qualitative case study design, data were collected through in-depth interviews, classroom observations, and document analysis involving school leaders, Islamic education teachers, students, and parents. Thematic analysis was conducted using socio-cognitive and ecological perspectives to examine the interplay between AI-supported administration, pedagogical practices, and students’ spiritual experiences. The findings indicate that AI improves administrative efficiency, transparency, and instructional management. However, excessive reliance on digital systems may increase cognitive load, reduce opportunities for reflective learning, and weaken students’ spiritual engagement when implemented without pedagogical and ethical guidance. Conversely, when embedded within a values-oriented learning ecology characterized by teacher mediation, reflective pedagogy, and spiritually supportive environments, AI fosters students’ self-regulation, moral awareness, and sense of responsibility. The study proposes a conceptual framework that positions AI as an integral component of a spiritually informed learning ecology, emphasizing that technological innovation should reinforce rather than diminish the core aims of Islamic education: spiritual growth, ethical development, and holistic learning. Abstrak: Integrasi cepat Kecerdasan Buatan (AI) dalam administrasi pendidikan dan pembelajaran menghadirkan peluang sekaligus tantangan bagi pendidikan Islam, khususnya terkait keterlibatan kognitif serta perkembangan spiritual dan moral peserta didik. Meskipun administrasi berbasis AI mampu meningkatkan efisiensi dan mendukung pengambilan keputusan berbasis data, implikasinya terhadap pembentukan spiritualitas siswa masih belum banyak dikaji. Penelitian ini bertujuan menganalisis pengaruh praktik administrasi berbasis AI terhadap lingkungan belajar dan perkembangan spiritual siswa di sekolah menengah Islam. Penelitian menggunakan pendekatan studi kasus kualitatif melalui wawancara mendalam, observasi kelas, dan analisis dokumen yang melibatkan kepala sekolah, guru pendidikan Islam, siswa, dan orang tua. Data dianalisis secara tematik dengan perspektif sosio-kognitif dan ekologis. Hasil penelitian menunjukkan bahwa AI meningkatkan efektivitas, transparansi, dan efisiensi administrasi pembelajaran. Namun, penggunaan yang berlebihan berpotensi meningkatkan beban kognitif, mengurangi refleksi, dan melemahkan keterlibatan spiritual apabila tidak disertai pertimbangan pedagogis dan etis. Sebaliknya, integrasi AI dalam ekologi pembelajaran yang berorientasi pada nilai, melalui bimbingan guru dan praktik reflektif, mampu memperkuat pengaturan diri, kesadaran moral, dan tanggung jawab siswa. Studi ini mengusulkan kerangka konseptual yang memosisikan AI sebagai bagian dari ekologi pembelajaran spiritual yang harus dikelola secara pedagogis untuk mendukung tujuan utama pendidikan Islam, yaitu pembentukan karakter, spiritualitas, dan pembelajaran holistik.